Conservation of complex adaptability uniqueness in different Deschampsia antarctica Desv. plant genotypes under standardized growth condition in vitro - Miryuta, N.; Poronnik, O.; Parnikoza, I.; Grahov, V.; Myryuta, G.; Kozub, N.; Sozinov, I.; Kunakh, V. (Ukrainian Antarctic Journal, 2016)
Uniqueness of complex adaptability index (united latent quality indicator of adaptability - ULQIA) has been shown to be taken place in plants having different chromosome number among Deschampsia antarctica Desv. (around Argentine Islands region, maritime Antarctic) cultivated under standardized growth condition in -vitro. ULQIA is assumed to express underlying in this plant adaptation process to uniqueness nature condition in dynamic hereditary memory special information in certain degree. It was shown that dynamic hereditary memory was saved in investigated plant genotypes under standardized growth condition in -vitro.